Implementation of Load Balancing and Failover Network Using Fortinet SDWAN Technology at PT. Lintasarta - Ghama Wellyandi (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
An Internet Service Provider (ISP) is a company or entity that provides internet connection services and other related services. The complexity of distribution control from several ISPs causes problems, especially in the speed factor, which affects the costs that must be incurred by the company. Management company information is not only focused on price and speed, but also requires good security and data traffic management (Traffic Engineering/TE). One application that is able to meet these needs is Software Defined Wide Area Network (SD-WAN). SD-WAN is the latest technological network development paradigm, overcoming the challenges that exist in network mechanisms in TE. The results of this study can be used as a comparison of several ISPs so that it can be known which one is better or which one to choose. Based on the results of the data analysis, the following conclusions were obtained: 1) As for the jitter problem in the performance of SD-WAN technology, it has advantages over ordinary conventional networks that do not use sdwan technology; 2) Regarding the delay/latency of internet service providers, SD-WAN has advantages over ordinary conventional networks and 3) With respect to packet loss, SD-WAN internet service providers have an advantage over ordinary conventional networks.